Comparative Life Cycle Assessment of Perovskite Solar Cell Production: Mesoporous n‐i‐p Versus Inverted p‐i‐n Architectures - Joana Príncipe; Luísa Andrade; Teresa M. Mata; António A. Martins (Advanced Energy & Sustainability Research)
Perovskite solar cells (PSCs) offer a viable alternative to silicon‐based technologies. Assessing their environmental performance is essential for a responsible development. This study compares the life cycle impacts of two PSC architectures, mesoporous n‐i‐p and inverted p‐i‐n, using the life cycle assessment methodology. The functional unit (FU) is a PSC with an active area of 2.88 cm2. The life cycle inventory uses primary production data complemented with literature, the EcoInvent v3.9.1 database, and process modeling. Environmental impacts are evaluated using the ReCiPe 2016 method in SimaPro v9.5.0.1. Results indicate that producing mesoporous PSCs has a higher environmental impact than producing inverted PSCs, due to differences in material and energy consumption. Specifically, mesoporous PSCs require about 132 MJ/FU compared to 25 MJ/FU for inverted PSCs, leading to carbon footprints of 14.1 kg CO2 eq./FU and 2.31 kg CO2 eq./FU, respectively. For inverted PSCs, energy consumption dominates the environmental impacts, accounting for around 80% of the total impact, while for mesoporous PSCs, depending on the environmental category, both materials and energy can dominate. Results highlight that energy consumption is critical and could be significantly reduced by using fully renewable electricity and/or minimizing the presence of metal in the back‐contact.